Dinamika Pengaruh Inflasi, Harga Minyak Dunia, dan Risiko Geopolitik terhadap Pertumbuhan Ekonomi Indonesia: Pendekatan Error Correction Model - Isni Maulida; Fitrawaty Fitrawaty; Arwansyah Arwansyah (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to analyze the influence of domestic and global factors on Indonesia’s economic growth, with variables including inflation, world oil prices, and geopolitical risk. The research employs a quantitative approach using a regression model combined with the Engle–Granger Error Correction Model (ECM) to capture both short-run and long-run dynamics among variables. The data used are time series data from 1986 to 2024, sourced from the World Bank and the Geopolitical Risk Index. The results show that in the short run, inflation and world oil prices have a positive and significant effect on economic growth, while geopolitical risk has a negative and significant effect. In the long run, inflation remains positive and significant, whereas geopolitical risk continues to have a negative and significant impact on economic growth. The error correction term coefficient (ECT(-1)), which is negative and significant, indicates the presence of a relatively fast adjustment mechanism toward long-run equilibrium. These findings confirm that the ECM approach is effective in explaining the dynamic relationship between domestic and global factors and Indonesia’s economic growth.